(untitled) (KULT_online, 2015)
The bilingual anthology Detective Fiction and Popular Visual Culture provides an interdisciplinary study of contemporary developments in detective fiction. Throughout the collection, the testing of generic conventions reveals a readjustment of the detective-fiction tradition to fit modern reader-viewers, ultimately raising the question: Is it detective fiction if the detective is spotlighted over the murder mystery case, or even the detective-fiction tradition itself?